Análisis del impacto del plan ADO en los resultados olímpicos españoles - Leiva Arcas, A.; Sánchez Pato, A.; Martínez Patiño, M.J. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2021)
In this article, Spanish sports policies and their influence on Olympic performance are analyzed, focusing on the program of Support for Olympic Sportsmen (ADO Plan, by the acronym in Spanish). It is described below how the ADO scholarships have been distributed and what has been the evolution of the Spanish Olympic participation under this program that supports the technification and professionalization of the national elite sport. The study continues with the analysis of the performance of Spanish athletes in the different editions of the Games within the development of this program, with special attention to the 2005-2016 period, emphasizing the relationship between the global economic contribution of the ADO Plan through scholarships and the results obtained. In conclusion, it can be seen that the ADO Plan has been one of the key factors in sports transformation in Spain and international successes since Barcelona 1992